2020
DOI: 10.1111/jvec.12380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vertebrate feces on the attraction of Culicoides (Diptera: Ceratopogonidae) in an Amazonian mangrove

Abstract: Biting midges are of interest to public health because they play an important role as vectors of disease‐causing pathogens, as well as being a biting nuisance to humans and domestic animals. Although these insects are common in mangrove areas, they have not yet been studied in this ecosystem in the state of Maranhão (MA), Brazil. The objective of this study was to characterize the Culicoides community structure found in a mangrove swamp and verify if the use of vertebrate feces as bait interferes with their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Different odors emitted by birds have been evaluated as attractants of vectors, from feces that attract mosquitoes (Cooperband et al, 2008) and biting midges (Fernandes-Rios et al, 2020), to bird feathers and skin that attract mosquitoes (Allan et al, 2006) and blackflies (Lowther and Wood, 1964;Weinandt et al, 2012). It has been also shown that mosquitoes are attracted to birds (Cornet et al, 2013a,b;Yan et al, 2018), or to odor from birds (Díez-Fernández et al, 2020), infected by avian malaria over non-infected or less infected birds (but see Tomás et al, 2008b;Martínez-de la Puente et al, 2009b;Lalubin et al, 2012 for contrasting results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different odors emitted by birds have been evaluated as attractants of vectors, from feces that attract mosquitoes (Cooperband et al, 2008) and biting midges (Fernandes-Rios et al, 2020), to bird feathers and skin that attract mosquitoes (Allan et al, 2006) and blackflies (Lowther and Wood, 1964;Weinandt et al, 2012). It has been also shown that mosquitoes are attracted to birds (Cornet et al, 2013a,b;Yan et al, 2018), or to odor from birds (Díez-Fernández et al, 2020), infected by avian malaria over non-infected or less infected birds (but see Tomás et al, 2008b;Martínez-de la Puente et al, 2009b;Lalubin et al, 2012 for contrasting results).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding chemical cues derived from birds that may be involved in host detection by blood-feeding flies, several odor sources have been investigated. For instance, mosquitoes (Cooperband et al, 2008) and biting midges (Fernandes-Rios et al, 2020) are attracted to traps baited with bird feces. Yet, odors emitted or derived from the uropygial gland of birds have been repeatedly suggested as major candidates involved in attraction of biting flies.…”
Section: Introductionmentioning
confidence: 99%